Immunohistochemical Evaluation and Clinicopathological Correlation of Mer and Axl Tyrosine Kinase TAM Receptors in Cutaneous Melanoma - Andrea Pontara; Giovanni Paolino; Vanesa Gregorc; Santo Raffaele Mercuri; Alessandra Bulotta; Pietro Bearzi; Claudio Doglioni; Nathalie Rizzo (Mattioli1885, 2020)
Background: Malignant melanoma (MM) is potentially the most dangerous form of skin tumor. In the last few years, the so-called TAM receptors, a unique family of tyrosine kinase (TK) receptors, have become increasingly important. Objectives: To evaluate Mer and Axl TAM receptor expression to find clinicopathological features that could explain the biological behavior of MM. Patients and Methods: Clinicopathological data were obtained from an MM electronic database at our Institute. We reviewed 24 cutaneous MM specimens. TAM receptor expression was assayed using immunohistochemistry. Combinative semiquantitative scoring was used for the evaluation of TAM receptor expression (MerTK and AxlTK). Appropriate statistical methods were used to evaluate a possible correlation between TAM receptor expression and the clinicopathological variables of the MM samples (univariate analysis and multivariate analysis). Results: MerTK and AxlTK were expressed differently in the MM samples, with a major expression of the first receptor. The cells of the tumor microenvironment contributed to the majority of the total score. A significant association was found between AxlScore and the site of the tumor and between AxlScore and the variable ulceration; another correlation was found between MerScore and the following characteristics: pathological stage of the tumor (pT), sex, ulceration, and tumor-infiltrating lymphocytes. Conclusions: All correlations between the expression of MerTK and AxlTK with the clinical and histological variables of MM should be validated in a large group of people in order to increase the validity and the impact of our observations, with subsequently therapeutic implications in the era of the "targeted therapy."